Association between weekend catch-up sleep and health-related quality of life of Korean adults. Issue 13 (March 2019) - Oh, Yun Hwan; Kim, HyeonJu; Kong, MiHee; Oh, Bumjo; Moon, Ji Hyun
Abstract : Abstract: Sleep debt is known to have harmful effects on health. Weekend catch-up sleep (CUS) is a behavior to cope with weekday sleep debt. However, it is unclear whether weekend CUS has advantageous effects on health because sleep hygiene guidelines recommend regularizing bed time and arousal time. The aim of this study was to identify whether weekend CUS behavior has an association with better health-related quality of life (HRQoL) According to the inclusion criteria, 4871 participants were selected from the 2016 Korea National Health and Nutrition Examination Survey. Sleep questionnaires and European quality of life scale-5 dimensions (EQ-5D) questionnaire were used to collect data about the participants' sleep patterns and HRQoL. Odds ratios (ORs) with 95% confidence intervals (95% CIs) for each dimensional problem of EQ-5D were derived by logistic regression. Mean EQ-5D index scores were compared between weekend CUS and non-CUS groups based on their weekday sleep durations and quintile of chronotype. The ORs of dimensional problems of HRQoL of non-CUS group versus weekend CUS group were 1.63 (95% CI 1.07, 2.47) for usual activities, and 1.45 (95% CI 1.11, 1.90) for anxiety/depression. Mean EQ-5D scores of the weekend CUS group were significantly higher than those of the non-CUS group for sleeping less than 6 hours (0.953 ± 0.004 vs 0.936 ± 0.007, P = .036) and sleeping 6 to 7 hours (0.965 ± 0.003 vs 0.955 ± .0.004, P = .045). These findings were similar in the fourth quintile (Q4) of chronotype (0.965 ± 0.007 vs 0.951 ± 0.008, P = .008) and fifth quintile (Q5) (0.952 ± 0.006 vs 0.941 ± 0.007, P = .022). Weekend CUS behavior was associated with better HRQoL than non-CUS among Korean adults. Especially, it was significant in participants who slept for less than 7 hours or participants whose chronotype was the fourth or fifth quintile. Attention may be needed for subjects with sleep short time and later chronotype who do not have weekend-CUS behaviors, because there is a risk that their HRQoL might be compromised.